Spatial and Multivariate Analysis, Random Sampling Error, and Analytical Noise: Empirical... - Robertson, Ian G. (American Antiquity, 1999)
Provides information on a study which examined how Bayesian methods can help archaeologists deal with problems inherent in variably-sized and small artifact samples. Information on the Teotihuacan Mapping Project; Discussion on Bayesian estimation of proportions; Empirical example from Teotihuacan; Conclusion.